2020
DOI: 10.1155/2020/8841752
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Safety of Transcutaneous Auricular Vagus Nerve Stimulation on Recovery of Upper Limb Motor Function in Subacute Ischemic Stroke Patients: A Randomized Pilot Study

Abstract: Background. Transcutaneous auricular vagus nerve stimulation (taVNS) is regarded as a potential method for recovery in stroke. The effectiveness of taVNS in acute and subacute stroke should be further discussed as previously, only a few small-scale trials have focused on chronic stroke patients. The objective of this study is to investigate the effect and safety of taVNS on upper limb motor function in subacute ischemic stroke patients. Methods. Twenty-one subacute ischemia stroke patients with single upper li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
141
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(148 citation statements)
references
References 51 publications
4
141
1
2
Order By: Relevance
“…Among which, four studies included chronic stroke patients ( Capone et al, 2017 ; Redgrave J.N. et al, 2018 ; Baig et al, 2019 ; Zhao B. et al, 2019 ) except one study included subacute ischemic stroke patients ( Wu et al, 2020 ). Here, we summarized the mainly functional improvement, parameters, side effects and future directions of nVNS in clinical studies on stroke.…”
Section: Clinical Trials To Assess Safety and Efficacy Of Non-invasiv...mentioning
confidence: 99%
See 2 more Smart Citations
“…Among which, four studies included chronic stroke patients ( Capone et al, 2017 ; Redgrave J.N. et al, 2018 ; Baig et al, 2019 ; Zhao B. et al, 2019 ) except one study included subacute ischemic stroke patients ( Wu et al, 2020 ). Here, we summarized the mainly functional improvement, parameters, side effects and future directions of nVNS in clinical studies on stroke.…”
Section: Clinical Trials To Assess Safety and Efficacy Of Non-invasiv...mentioning
confidence: 99%
“…Researchers recently published a randomized pilot study exploring the safety and effectiveness of taVNS in treating patients with subacute ischemic stroke. In this study, 21 patients with strokes in the acute or subacute phase (between 0.5 and 3 months post onset) were included ( Wu et al, 2020 ). At the endpoint, there were significantly greater improvements in FMA-U, FIM, and WMFT scores in the taVNS group compared with the sham-taVNS group.…”
Section: Clinical Trials To Assess Safety and Efficacy Of Non-invasiv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, direct brain stimulation of targets, such as the basal forebrain, could be used to provide more specific neuromodulation to achieve key therapeutic results. Lastly, less invasive techniques, such as auricular VNS might still be able to convey therapeutic benefits if their stimulation protocols and target activation within the central nervous system is optimized 95,96 . The data presented here provide a framework for dissecting the role of VNS within specific therapeutic indications, with the ultimate goal of improving therapeutic delivery and patient outcomes.…”
Section: Optimizing Vns To Treat Neurological Conditionsmentioning
confidence: 99%
“…To date, clinical and laboratory research demonstrated that taVNS can improve lung function (19,20). In addition, taVNS is commonly used to treat encephalopathy, encephalitis, ischemic infarcts, cerebral venous thrombosis, as well as peripheral nervous system pathologies [i.e., muscle injuries, and peripheral neuropathies; (21)(22)(23)(24)(25)(26)].…”
mentioning
confidence: 99%